Phosphorus Electrodes in Sodium Cells: Small Volume Expansion by Sodiation and the Surface‐Stabilization Mechanism in Aprotic Solvent. Issue 3 (21st January 2014) - Yabuuchi, Naoaki; Matsuura, Yuta; Ishikawa, Toru; Kuze, Satoru; Son, Jin‐Young; Cui, Yi‐Tao; Oji, Hiroshi; Komaba, Shinichi
Abstract The electrode performance of amorphous phosphorus in aprotic Na cells is examined. Amorphous phosphorus is electrochemically reduced in the Na cells with a three‐electron redox process, crystallizing into Na3P. NaP bonds in Na3P have high covalent characteristics. Therefore, the molar volume of Na in Na3P is anomalously small in comparison to other Na–metal alloys that have been used as negative electrode materials. The theoretical volumetric capacity, calculated at full volume expansion of amorphous phosphorus electrodes through sodiation, is expected to be 27 % larger than that of metallic sodium. However, experimentally, it is found that severe electrolyte decomposition results in insufficient reversibility of the electrode materials, owing to the highly reactive Na3P surface. Electrode reversibility is successfully improved by utilizing an electrolyte additive, fluoroethylene carbonate (FEC). The surface chemistry of phosphorus in the aprotic solvent with sodium salts is examined by hard/soft X‐ray photoelectron spectroscopy (PES). PES studies reveal that FEC effectively stabilizes the solid–electrolyte interphase (SEI), containing monovalent phosphorus species and sodium fluoride, and thus electrolyte decomposition is partly suppressed by the relatively stable SEI formed on the surface of phosphorus particles.